2000
DOI: 10.1046/j.1365-2249.2000.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Blister fluid T lymphocytes during toxic epidermal necrolysis are functional cytotoxic cells which express human natural killer (NK) inhibitory receptors

Abstract: SUMMARYToxic epidermal necrolysis (TEN) is a rare life-threatening adverse drug reaction characterized by a massive destruction of the epidermis. Immunohistological studies of skin biopsies of TEN showed infiltrates of predominantly CD8 þ T lymphocytes even though other authors reported a prominent involvement of cells of the monocyte-macrophage lineage. The aim of this study was to characterize phenotypically and functionally the cells present in the cutaneous blister fluid of four patients with TEN. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
116
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 23 publications
10
116
0
6
Order By: Relevance
“…Goat F(abЈ) 2 anti-human IgG Fc was purchased from Beckman Coulter. mAbs to human CD3 (HIT3a), forkhead box P3 (Foxp3; PCH101), and the isotype controls to Foxp3 were purchased from eBioscience.…”
Section: Abs and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goat F(abЈ) 2 anti-human IgG Fc was purchased from Beckman Coulter. mAbs to human CD3 (HIT3a), forkhead box P3 (Foxp3; PCH101), and the isotype controls to Foxp3 were purchased from eBioscience.…”
Section: Abs and Reagentsmentioning
confidence: 99%
“…Although many factors that cause variability in the clinical course have been suggested, it remains unknown which factors are predominantly involved in the process. Because the most prevalent severe drug eruptions are thought to be mediated by drug-reactive T cells (1)(2)(3)(4), the phenotype and functions of these effector T cells are likely to determine the clinical picture of the disease. However, investigators need to be made aware of the alternative view that severe drug eruptions are due to a dysbalance of the immune system caused by excessive activation of effector T cells and an inadequately low function or number of T cells that can limit immunopathology.…”
mentioning
confidence: 99%
“…2002 yılında bildirdikleri olguda bül sıvısı içerisinde lenfosit ağırlık-lı hücresel dağılım bulunduğu-nu bildirmişlerdir. T lenfositleri arasında da en sık CD3+ ve CD8+ ağırlıklı oldukları bildirilmiştir (10,11).…”
Section: Discussionunclassified
“…Prior reports that used immunolabeling to characterize the effector cells ofthe epidermal injury in SJS/TEN obtained conflicting results (13,(17)(18). It is conceivable that CD8+ T lymphocytes are important in initiating the death ofkeratinocytes in SJSI TEN (19), while monocyte-macrophage populations playa pivotal role at the late stage of SJS/TEN. In our study, we found that the epidermal infiltrate was predominantly composed of CD8+ T lymphocytes, this finding confirming the skin biopsy specimens taken at early stage of disease.…”
Section: Pi: Steven-johnson Syndrome (Sjs) Versus Healthy Skin (Hs) Pmentioning
confidence: 99%